Biochar-mediated remediation of uranium-contaminated soils: evidence, mechanisms, and perspectives - Fengyu Huang; Faqin Dong; Li Chen; Yi Zeng; Lei Zhou; Shiyong Sun; Zhe Wang; Jinlong Lai; Linchuan Fang (Biochar, 2024)
Abstract Soil contamination by uranium presents a burgeoning global environmental concern, exerting detrimental effects on both agricultural production and soil health. Biochar, a carbonaceous material derived from biomass pyrolysis, exhibits considerable potential for remediating uranium-contaminated soils. However, a comprehensive review of the effects of biochar on the fate and accumulation of uranium in soil–plant systems remains conspicuously absent. In this paper, uranium sources and contamination are reviewed, and the impact of biochar on uranium immobilization and detoxification in soil–plant systems is analyzed. We reviewed the status of uranium contamination in soils globally and found that mining activities are currently the main sources. Further meta-analysis revealed that biochar addition significantly reduced the soil uranium bioavailability and shoot uranium accumulation, and their effect value is 58.9% (40.8–76.8%) and 39.7% (15.7–63.8%), respectively. Additionally, biochar enhances the soil microenvironment, providing favourable conditions for promoting plant growth and reducing uranium mobility. We focused on the mechanisms governing the interaction between biochar and uranium, emphasising the considerable roles played by surface complexation, reduction, ion exchange, and physical adsorption. The modification of biochar by intensifying these mechanisms can promote uranium immobilisation in soils. Finally, biochar alleviates oxidative stress and reduces uranium accumulation in plant tissues, thereby mitigating the adverse effects of uranium on plant growth and development. Overall, our review highlights the capacity of biochar to remediate uranium contamination in soil–plant systems through diverse mechanisms, providing valuable insights for sustainable environmental remediation. Highlights Biochar reduces uranium mobility through a variety of mechanisms, including surface complexation, reduction, ion exchange, and physical adsorption. Biochar significantly reduces uranium bioavailability in soil and limits its accumulation in plants. Modified biochar has been shown to enhance its effectiveness in immobilising uranium. Biochar application to soil not only promotes uranium remediation but also improves soil quality. Graphical Abstract